Assessments of 16 Exploited Fish Stocks in Chinese Waters Using the CMSY and BSM Methods - Zhai, Lu; Liang, Cui; Pauly, Daniel (Frontiers in Marine Science, 2020)
Sixteen marine fish species (populations) exploited by Chinese fisheries were assessed, using published time series of catch and the CMSY and BSM methods. Given the catch times series as inputs, some ancillary information and reasonable constraints, carrying capacity, maximum sustainable yield, and likely time series of biomass and exploitation rate were estimated. The results show that one (7%)of the assessed species was severely depleted, four species(27%) were fully/overfished, six(40%) were outside of safe biological limits, one species(7%) was recovering and three species(20%) were in a healthy state at the end year of their assessment. However, one species, Pacific sardine (Sardinops sagax), could not be assessed using CMSY, as the exceedingly large fluctuations of its biomass were mainly environmentally driven. These results correspond with previous knowledge on the status of fish populations along the coast of China, where overfishing is rampant. Based on these assessments, some of the benefits that would result from a reduction of the excessive fishing effort are outlined.